2022
DOI: 10.1016/j.chom.2021.11.013
|View full text |Cite
|
Sign up to set email alerts
|

The antibody response to SARS-CoV-2 Beta underscores the antigenic distance to other variants

Abstract: Highlights d Generated 674 antibodies from patients infected with SARS-CoV-2 Beta variant d 18 of 27 most potent mAbs target the 3 mutations in Beta RBD d A major response to N501Y includes a public IgVH4-39 sequence d Two antibodies recognize a neutralizing epitope conserved between SARS-CoV-1 and -2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
101
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(111 citation statements)
references
References 50 publications
9
101
1
Order By: Relevance
“…In addition to concordant epitope targeting, we also found consistent V gene usage in the antibody response to all three variants we investigated. Although some recent studies have noted enrichment for IGHV4-39 and closely related V H genes in Beta-infection ( 56, 57 ) we did not observe any differences in the usage of these genes. Our findings likely highlight the difference between the neutralizing antibody repertoires investigated in prior studies compared to the total binding repertoires examined here and emphasize the insights to be gleaned by taking a broader perspective.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In addition to concordant epitope targeting, we also found consistent V gene usage in the antibody response to all three variants we investigated. Although some recent studies have noted enrichment for IGHV4-39 and closely related V H genes in Beta-infection ( 56, 57 ) we did not observe any differences in the usage of these genes. Our findings likely highlight the difference between the neutralizing antibody repertoires investigated in prior studies compared to the total binding repertoires examined here and emphasize the insights to be gleaned by taking a broader perspective.…”
Section: Discussioncontrasting
confidence: 99%
“…Recent studies have shown that Y501-dependent mAbs derived from IGHV4-39 and related genes are overrepresented among neutralizing antibodies isolated from Beta-infected individuals ( 56, 57 ). Structural evidence suggests that bias toward these genes may in part be due to germline-encoded residues Y35 and Y54 in complementarity-determining region (CDR) H1 and H2, respectively ( 56 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several of these have been designated variants of concern (VoC) (https://www.cdc.gov/coronavirus/2019-ncov/variants/variantclassifications.html) and have led to successive waves of infection: first Alpha (Supasa et al, 2021), then Delta (Liu et al, 2021a), then Omicron (Dejnirattisai et al, 2022) spread globally becoming the dominant variants. Alongside these, Beta (Zhou et al, 2021) and Gamma (Dejnirattisai et al, 2021b) case-numbers/variants-distribution-of-case-data-29-april-2022#omicron) and, although the disease is less severe, particularly in the vaccinated, the scale of the outbreak has still led to a large number of deaths (Nealon and Cowling, 2022).…”
mentioning
confidence: 99%
“…Mutation of the ACE2 interacting surface may also give advantage by increased ACE2 affinity for S, or possibly altering receptor tropism (Zahradnik et al, 2021). Increased ACE2 affinity has been found in VoC compared to ancestral strains (Dejnirattisai et al, 2021b;Liu et al, 2021a;Supasa et al, 2021;Zhou et al, 2021), potentially conferring a transmission advantage, but affinity is not increased in Omicron BA.1 (Dejnirattisai et al, 2022) and only marginally in BA.2 (Nutalai et al, 2022).…”
mentioning
confidence: 99%